1994
DOI: 10.1177/019459989411000208
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative pathology of the intraepithelial laryngeal neoplasia

Abstract: A clinical-histologic and morphometric study on 32 patients with precancerous laryngeal lesions was carried out. Two biopsies taken at different times were studied, and the cases in which carcinoma developed were compared with those cases in which it did not. The only clinical-histologic variable with prognostic value, related with evolution to carcinoma, was severe dysplasia. The Malignancy Grading System, which grouped together 13 clinical-histologic variables, had both high sensitivity and high specificity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…Several studies have reported widely varying malignant transformation rates (MTR) of between 6% and 74% . However, it is extremely difficult to precisely analyze these data from several studies, because the severity grading of the atypia is not standardized, and different approaches for diagnosis are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported widely varying malignant transformation rates (MTR) of between 6% and 74% . However, it is extremely difficult to precisely analyze these data from several studies, because the severity grading of the atypia is not standardized, and different approaches for diagnosis are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoma transformation rate of laryngeal dysplasia varies largely from 2% to 74% among investigated cases. 8,9 A recent meta-analysis has shown that laryngeal dysplasia lesions has a 14% overall transformation rate (95% confidence interval [CI], [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and the malignant transformation risk is higher with increased severity of dysplasia grade. 10 Laryngeal dysplasia remains one of the most controversial topics in laryngeal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal dysplasia is a premalignant condition reported to affect between 2 and 10 per 100,000 of the population 1. Studies vary widely in their reported malignant transformation rates from 2% to 74% of cases 2, 3. A recent meta‐analysis has shown an overall transformation rate of 14% (95% confidence interval [CI] 8% to 22%) for laryngeal dysplastic lesions 4…”
mentioning
confidence: 99%